Cryopreservation as Biotechnological Application of Dendritic Cells in Clinical Practice - Goltsev , Anatoliy; Yampolska, Katerina; Kisielova, Hanna; Оstankov Maksym; Dubrava , Tatiana; Babenko, Natalya; Gaevska, Yuliya; Bondarovych, Mykola (Problems of Cryobiology and Cryomedicine, 2021)
An important component of the pathogenesis of autoimmune diseases is the immune system deregulation as an impaired tolerance to its own antigens by reducing the content of T-regulatory cells. Their formation is closely related to the function of dendritic cells (DCs), so in autoimmune diseases the use of DCs with tolerogenic potential is promising for the restoration of antigen-specific tolerance. Recently, the issue of establishing the banks of tolerogenic DCs for clinical use, which involves their cryopreservation, has been actively discussed. To date, there is no common protocol for DCs freezing, which would take into account the different sources of their obtaining, the initial structural and functional state before freezing, composition of cryopreservation media and other factors. The review summarizes experimental data on cryopreservation of peripheral blood and bone marrow mononuclear cells or monocytes. The potential for their further ex vivo differentiation into DCs to ensure the stability of immature phenotype and tolerogenic function has been studied. Probl Cryobiol Cryomed 2021; 31(4): 289–303